Facile synthesis of a mesostructured TiO2–graphitized carbon (TiO2–gC) composite through the hydrothermal process and its application as the anode of lithium ion batteries. Issue 45 (20th April 2016) - Sohn, Hiesang; Kim, Daeun; Lee, Jinwoo; Yoon, Songhun
Abstract : A mesostructured TiO2 –graphitic carbon (TiO2 –gC) composite was synthesized through a simple and scalable one-step hydrothermal method, exhibiting high capacity, advanced rate capability and a very stable cycle life. Abstract : A mesostructured TiO2 –graphitic carbon (TiO2 –gC) composite was synthesized through a simple and scalable hydrothermal method to be employed as an anode material in Li-ion batteries. In a wide voltage range (0.0–2.5 V), the TiO2 –gC composite anode possesses a high initial lithiation capacity (598 mA h g −1 ) at 0.1 C (1 C: 150 mA g −1 ), and it still retains 369 mA h g −1 after 50 cycles at 0.5 C. Furthermore, under a high current density of 2 C, the TiO2 –gC anode exhibits stable capacity (252 mA h g −1 ) retention for up to 200 cycles. This excellent electrochemical performance could be ascribed to a synergistic effect of well-developed mesoporosity with a high surface area (345.4 m 2 g −1 ), the conductive graphitic carbon wall, and uniformly dispersed TiO2 nanoparticles, resulting in improved Li + penetration, fast electron transport and high structural stability during cycling.